A model for adapting clinical guidelines for electronic implementation in primary care. - Lobach, D. F. (American Medical Informatics Association, 1995)
Medical informaticians who seek to implement clinical guidelines by computer must be aware of a significant gap that exists between guideline development and utilization. In order to be effective, guideline recommendations must be followed by clinicians; in order for clinicians to follow willingly, they must agree with the guidelines. This paper presents a model process for building consensus among clinicians that can be used to obtain support for guideline recommendations prior to their electronic implementation. This approach involves initial presentation of the guidelines by a specialist, iterative cycles of surveying clinicians' opinions about the guidelines and revising the guidelines, supervision of the process by a practice opinion leader, and final group discussion of the revised guidelines to reach consensus. This model was successfully used to adapt guidelines for the continuing care of patients with diabetes mellitus that were subsequently implemented electronically with broad support of the primary care clinicians using them. The model minimized the need for lengthy group discussion by surveying individuals' attitudes and working through a practice opinion leader to gain consensus support for the guidelines. An efficient approach for developing support for guidelines among practitioners will facilitate the electronic implementation of guidelines and lead to enhanced compliance with guidelines after implementation.